2020
DOI: 10.1080/14631377.2020.1827202
|View full text |Cite
|
Sign up to set email alerts
|

The footprints of COVID-19 on Central Eastern European stock markets: an intraday analysis

Abstract: This study analyses the intraday multifractal behaviour of three Central Eastern European stock markets by deploying five-minute index data ranging from December 2019 to May 2020. With the analysis of multifractality, we can evaluate the degree of efficiency of the stock markets analysed. We divided the whole sample into three different periods of about two months each. Data for the Czech Republic, Hungary and Poland are used and their behaviour is compared with Germany (as a benchmark of the European Union) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…European countries are greatly affected by the first and second waves of Covid-19, compared to Asia, and herding behavior can also be seen in the second quarter. However, Spain is the most affected country in Europe and herding behavior is evident in all quarters except for the first, which is in line with the results of Aslam et al ( 2020e ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…European countries are greatly affected by the first and second waves of Covid-19, compared to Asia, and herding behavior can also be seen in the second quarter. However, Spain is the most affected country in Europe and herding behavior is evident in all quarters except for the first, which is in line with the results of Aslam et al ( 2020e ).…”
Section: Discussionsupporting
confidence: 91%
“…We find a growing number of studies on the financial impacts of the Covid-19 pandemic. Recently, various themes have been developed, including financial networks (Aslam et al, 2020c ; Zhang et al, 2020 ), stock market reactions (Aslam et al 2020e , 2021 ; Haroon & Rizvi, 2020 ; Zhang et al, 2020 ), exchange rate fluctuation during the pandemic (Aslam et al, 2020b ; Njindan Iyke, 2020 ), oil market reactions (Apergis & Apergis, 2020 ; Devpura & Narayan, 2020 ), air quality performance and multifractality (Ming et al, 2020 ; Sipra et al, 2021 ), insurance (Wang et al, 2020 ) and gold and cryptocurrencies (Corbet et al, 2020 ). The Covid-19 pandemic has also affected the efficiency of different financial markets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yong-Ming, Jais, and Chan (2020) showed that higher numbers of COVID-19 cases in Malaysia promoted negative impact on the KLCI index and all sectorial indices, except for the Real Estate Investment Fund (REIT). Faheem, Francisca, Mariana, Paulo, and Mughal (2021) demonstrated that the degree of multifractality changes in the different time periods, moreover, the behavior of these stock markets changed from persistent to anti-persistent ones. Gurmeet and Muneer (2021) suggested that there was a significant impact of COVID-19 on world stock markets, however, the impact is varied for developed and emerging countries.…”
Section: Existing Studiesmentioning
confidence: 99%
“…Researchers have applied MFDFA in a variety of financial time series such as stock markets [42][43][44][45], foreign exchanges [46,47], cryptocurrency market [48,49], gold [50], futures market [51,52], green bonds [53], and the carbon emission trading market [54]. For example, Aslam et al [43] used MFDFA to examine the multifractal characteristics of MSCI in emerging Asian markets.…”
Section: Introductionmentioning
confidence: 99%